Carajás: updating and commented bibliography on studies conducted by Museu Paraense Emílio Goeldi - Secco, Ricardo de Souza; do Rosário, Alessandro Silva; Ruivo, Maria de Lourdes Pinheiro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Documentary information on the Serra dos Carajás, compiled by the year of 1983, were published in two volumes by the Museu Paraense Emílio Goeldi. Such volumes did not include information on most of the environmental and biodiversity studies made in the area, with the participation of researchers from the Museu Goeldi. Currently, there is a growing demand for information on the subject, which has been found through numerous inquiries made by Brazillian and foreign researchers, notably on the fauna, flora and the environment of that region. Thus, the aim of this survey is to provide an updated and commented compilation on the researches conducted in Carajás by scientists of the institution and cooperators, as a complementary appendix to this special number.